From Paramagnetic to Single‐Molecule Magnet Behaviour in Heterobimetallic Compounds Containing the Tetrakis(thiocyanato‐κN)cobaltate(II) Anion. Issue 6 (13th February 2018) - Kalinke, Lucas H. G.; Cardoso, Jocielle C. O.; Rabelo, Renato; Valdo, Ana K.; Martins, Felipe T.; Cano, Joan; Julve, Miguel; Lloret, Francesc; Cangussu, Danielle
Abstract : Four heterobimetallic compounds of formula [Ni(Me6 trans [14]dieneN4 )][Co(NCS)4 ] (1 and2 ), [Ni(Me6 trans [14]dieneN4 )]2 [Co(NCS)4 ](ClO4 )2 · H2 O (3 ) and [Ni(Me6 trans [14]dieneN4 )]2 [Co(NCS)4 ](PF6 )2 (4 ) (Me6 trans [14]dieneN4 = 5, 7, 7, 12, 14, 14‐hexamethyl‐1, 4, 8, 11‐tetraazacyclotetradeca‐4, 11‐diene) have been synthesised and structurally characterised. Their structures are formed of square‐planar [Ni(Me6 trans [14]dieneN4 )] 2+ cations and tetrahedral [Co(NCS)4 ] 2– anions. The variable‐temperature magnetic properties of2 –4 mainly obey the zero‐field splitting effects ( D ) of the 4 A2 ground‐state term of the pseudo‐tetrahedral [Co(NCS)4 ] 2– anionic complex (2 D is the energy gap between the |±1/2> and |±3/2> levels of the spin quadruplet when E = 0), the square‐planar nickel(II) unit being diamagnetic. Analysis of their magnetic data through the spin Hamiltonian H = D [ S z 2 – S ( S + 1)/3] + E ( S x 2 – S y 2 ) + gβHS led to the following best‐fit parameters: g = 2.216(17), D = +3.74(12) cm –1 and E/D = 0.0137(6) for2, g = 2.335(20), D = +11.6(4) cm –1 and E/D = 0.002(4) for3 and g = 2.298(15), D = +7.29(17) cm –1 and E/D = 0.068(3) for4 . The Q‐band EPR spectra of powdered samples of2 –4 in the temperature range 4.0–20 K support the positive signs of D . With an applied dc field, the ac susceptibility data for3 and4 below 4.5 K reveal a slow magnetic relaxation, which is a characteristic of single‐ion magnet (SIM) behaviour. Abstract : Slow relaxation of the magnetisation has been observed in compounds containing the [Co(NCS)4 ] 2– complex anion, the geometry of which strongly deviates from ideal T d .